2014
DOI: 10.4085/1062-6050-49.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Workplace Bullying Among Athletic Trainers in the Collegiate Setting

Abstract: Workplace bullying incidents occur when administrators tolerate bullying behaviors from controlling and manipulative individuals who lack respect for the athletic training professional. Several negative outcomes result from bullying interactions, including stress and anxiety; WPB is dealt with by learning to be more emotionally resilient and avoiding confrontations. Workplace training is needed to prepare athletic trainers for such negative experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…The setting is becoming more popular and of great interest for newly credentialed ATs, and thus, understanding more about the experiences of ATs in this setting is imperative. Recent studies 16,17 revealed that WPB was occurring in the collegiate setting, another popular workplace; however, the expectations and demands can vary from those in the secondary school setting. The purpose of our study, therefore, was to examine the prevalence of WPB among ATs in the secondary school setting and identify the personnel involved in the bullying acts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The setting is becoming more popular and of great interest for newly credentialed ATs, and thus, understanding more about the experiences of ATs in this setting is imperative. Recent studies 16,17 revealed that WPB was occurring in the collegiate setting, another popular workplace; however, the expectations and demands can vary from those in the secondary school setting. The purpose of our study, therefore, was to examine the prevalence of WPB among ATs in the secondary school setting and identify the personnel involved in the bullying acts.…”
Section: Discussionmentioning
confidence: 99%
“…19 The research design was borrowed from our previously published studies 16,17 examining WPB in the collegiate setting. A cross-sectional survey was first used to examine the prevalence of WPB and individuals' experiences with bullying events-this constituted phase I of the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In the athletic training literature, workplace bullying has also been used to describe negative interactions between ATs and the individuals they work with, including coaches. [3][4][5] The values of ATs and coaches are often dichotomous, and pressure to make premature return-to-play decisions, either to satisfy a coach or for job security, does not allow ATs to operate in the best interests of athletes. For this reason, as indicated by the National Athletic Trainers' Association (NATA) and 5 other medical associations, 1 a coach should never be the primary supervisor of team physicians or ATs or have influence on the employment status of these medical professionals.…”
mentioning
confidence: 99%